Appalachian Women : An Annotated Bibliography - Farr, Sidney Saylor, 1932- (Book collections on Project MUSE., 1981)
Appalachian women have been the subject of song, story, and report for nearly two centuries. Now for the first time a fully annotated bibliography makes accessible this large body of literature. Works covered include novels, short stories, magazine articles, manuscripts, dissertations, surveys, and oral history tapes -- altogether over 1,200 items. The annotated listings are grouped under broad subject headings, including biography, coal mining, education, fiction, health care, industry, migrants, music, poetry, and religion. An author/title/subject index provides easy access to the listings.